Inroads for HIV prevention among men: findings from mixed methods research in the context of the DREAMS partnership in Southern Africa. (15th June 2022) - Gottert, Ann; Pulerwitz, Julie; Heck, Craig J.; Shabangu, Patrick; Lukhele, Bhekumusa; Cawood, Cherie; Khanyile, David; Apicella, Louis; Okal, Jerry; Mathur, Sanyukta
Abstract : Objective: To assess trends in men's HIV risk factors and service use, and their experiences with prevention programming, during an intensive HIV response for adolescent girls and young women and their male partners. Design: Independent cross-sectional surveys in 2016–2017 and 2018 with men in Eswatini (20–34 years-old, n = 1391) and Durban, South Africa (20–40 years-old; n = 1665), complemented by 74 in-depth interviews (IDIs) with men exposed to HIV services/prevention programming. Methods: Survey recruitment was primarily at hot-spot venues. We assessed Round 1–2 trends in HIV risk factors and service use, overall and by HIV risk profiles. IDI respondents were identified via survey responses or program partners. Results: HIV risk factors were prevalent in both countries at each survey round, although there were reductions over time among the highest risk profiles in South Africa. Most men were engaged in HIV services (e.g. nearly two-thirds tested for HIV in the last year at round 2, with large increases in Eswatini). Qualitative data suggest HIV service uptake was facilitated by increased convenience and supportive information/messaging about HIV treatment efficacy. Men described eagerly receiving the information and support offered in HIV prevention programming, and effects on HIV risk reduction and newly engaging in HIV services. However, less than 15% of survey respondents reported being reached by such programming. Conclusion: Important inroads have been made to engage men in HIV services and prevention programming in the two countries, including among the high-risk profiles. Still, improving coverage of comprehensive HIV prevention programming is critical, particularly for men most at risk.